Responsabilidad social empresarial, costos de transacción y competitividad sectorial en servicios públicos - Congote Ochoa, Bernardo (2023)
Citizen participation, like the notion of corporate social responsibility derived from it, is not seen favorably by the utilities sector. Some consider it as an imposition, when it really is the result of a political consensus laid down by the Constitution. Others see it as a form of entertainment that the Colombian Congress turned into Law 142 of 1994, when in truth it is a qualitative improvement in legislation in this industry. There are others still who understand it as the product of idle political scientists, when it really is the most significant political landmark since the breakdown of the colonial pact at the beginning of the XIX century. The purpose of this article is to show that the democratic notion of citizen participation, laid down by the 1991 Constitution, is a powerful tool to assist the utilities sector in going from being merely competitive to being highly competitive. The basic assumption is that, given the tendency we would find in variable production costs to become equally low, the chances of competing profitably in the global market could therefore be concentrated now in producing notable differences in fixed costs, one of which would be ìtransaction costs.î